Dendrothele latenavicularis sp. nov. (Agaricales, Basidiomycota) from the Patagonian Andes - Gorjón, Sergio P. (2011)
Dendrothele latenavicularis is described as a new species from the Patagonian Andes forest. It is closely related to other species of Dendrothele with navicular or arachiform basidiospores-D. arachispora, D. cymbiformis D. navicularis, D. magnenavicularis, and D. pitrae-but with distinctly broader basidiospores. A key to the previous species is included.